THE ROLE OF NUTRITION IN BRAIN DEVELOPMENT - Dana-Teodora; Ana Simona Drochioi; Oana Teslariu (Amaltea Medical Publishing House, 2016)
The brain is an organ that functions harmoniously special only through a balanced intake of biologically active substances. The phrase "food for brain" expresses the important role of nutrition in the development and energy supply of the brain. There is a brief presentation of data on the development of the brain, the existence and functionality of the microbiome-gut-brain axis and the impact of the key nutrients in these complex processes. The authors concluded that nutritional assistance to the pregnant woman since the onset of pregnancy, the prophylaxis of prematurity, the early prevention of the gut microbiome of infant through encouragement of natural birth and breast-feeding are necessary conditions for the development of the brain.